2016
DOI: 10.1002/pat.3977
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of functional carbon nanotubes and graphene oxide on the anti-corrosion performance of epoxy coating

Abstract: In this work, we reported the synergistic effect of functional carbon nanotubes (CNTs) and graphene oxide (GO) on the anticorrosion performance of epoxy coating. For this purpose, the GO and CNTs were firstly modified by the 3aminophenoxyphthalonitrile to realize the nitrile functionalized graphene oxides (GO-CN) and carbon nanotubes (CNTs-CN). As modified GO-CN and CNTs-CN were characterized and confirmed by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and gravimetric analyzer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…It provides the values of corrosion current (Icorr) and corrosion potential (Ecorr) for uncoated Al substrate, neat epoxy coating, and MWCNT/epoxy coating, represented by Tafel plots in Figure . It is well known that the low Icorr and more positive values of Ecorr contributes to enhanced corrosion protection performance . Here, the anodic dissolution of uncoated Al metal was verified with higher Icorr and lower Ecorr values in both mediums.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…It provides the values of corrosion current (Icorr) and corrosion potential (Ecorr) for uncoated Al substrate, neat epoxy coating, and MWCNT/epoxy coating, represented by Tafel plots in Figure . It is well known that the low Icorr and more positive values of Ecorr contributes to enhanced corrosion protection performance . Here, the anodic dissolution of uncoated Al metal was verified with higher Icorr and lower Ecorr values in both mediums.…”
Section: Resultssupporting
confidence: 64%
“…The uncompromising use of metals with increasing urbanization has caused a great easement in the standard of living, but with a heavy price tag, the metal corrosion. The corrosion associated with the use of metals is considered as a major environmental and economic catastrophe . In order to address this serious problem, scientists have introduced several protective coatings over metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature review, anticorrosion coatings in terms of GO-based epoxy composites were found to attract extensive academic and industrial research interests than other GO-based polymer composites in the past decades. For example, He et al [30] presents that incorporation of GO into epoxy resin significantly enhanced anticorrosion performance on the metallic substrate due to the improved corrosion factor in electrolyte barrier properties derived from highly aspect and dispersed graphene platelets in epoxy coating [31]. Thus, epoxy/graphene composite coatings can be considered as promising candidates for protective coatings in the nuclear industry.…”
mentioning
confidence: 99%
“…However, some micro-holes and cracks will occur during the curing process of waterborne epoxy coating, which lead to reduction of coatings' anti-corrosive properties. One of the effective methods for improving the corrosion resistance of the waterborne epoxy coating is adding nano pigments, such as mesoporous materials [3][4][5][6][7][8], layered materials [9][10][11], metal-organic frameworks [12,13] and so on. In our previous work, ZSM-5 [14], mesoporous-TiO 2 [15,16], layered double hydroxides and metal-organic frameworks [17] have been investigated as anti-corrosive pigments.…”
Section: Introductionmentioning
confidence: 99%